2013
DOI: 10.1021/nn400671z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Contact Resistance in Graphene Devices through Contact Area Patterning

Abstract: Performance of graphene electronics is limited by contact resistance associated with the metal-graphene (M-G) interface, where unique transport challenges arise as carriers are injected from a 3D metal into a 2D-graphene sheet. In this work, enhanced carrier injection is experimentally achieved in graphene devices by forming cuts in the graphene within the contact regions. These cuts are oriented normal to the channel and facilitate bonding between the contact metal and carbon atoms at the graphene cut edges, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
219
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(232 citation statements)
references
References 45 publications
(79 reference statements)
6
219
0
Order By: Relevance
“…Selected graphene monolayers were contacted using electron [14] and other factors may contribute the transparency of the interface, so that graphene defectiveness may not necessarily be detrimental. Reduction of the specific contact resistance has been achieved by O2 plasma damaging [15] or by intentional pitting [16] or cutting [17] of graphene in the contact region.…”
Section: Methodsmentioning
confidence: 99%
“…Selected graphene monolayers were contacted using electron [14] and other factors may contribute the transparency of the interface, so that graphene defectiveness may not necessarily be detrimental. Reduction of the specific contact resistance has been achieved by O2 plasma damaging [15] or by intentional pitting [16] or cutting [17] of graphene in the contact region.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical reports estimated that the contact resistivity could be as low as 10 to 10 3 times the facial contact based on a quantum tunneling process [57]. Very recently, contact modules considering the edge contact resistance were developed [80]. The proposed contact module results in an improvement of approximately 20~60% compared to the conventional method involving a lift-off process.…”
Section: Process Dependence On the Contact Resistancementioning
confidence: 99%
“…It is notable that the cuts are not extended to the end of graphene, which would result in a comb pattern. Smith et al fabricated the rail-patterned graphene device using different number of cuts to increase the perimeter length of graphene for their study on the device performance based on the amount of cuts made [53]. Their TLM measurements yielded a contact resistance of 125 Ω·μm post-anneal with 10 cuts under Cu contact, compared to 184 Ω·μm post-anneal without any patterns, which proves that the patterns provide a better device performance via covalent contacts.…”
Section: Patterning the Graphene At The Device Interfacementioning
confidence: 99%
“…Furthermore, their study showed that as the perimeter length increased, more areas of graphene become available for covalent contacts, and a decrease in the total resistance of the device post-anneal was first seen. Yet, as the number of cuts increased beyond 8, an upturn of the resistance was shown because extreme narrowing of the width of the graphene nanoribbons by making too many cuts had led to quantization effects that impeded carrier transfer at the interface [53]. Because this pattern works best under optimal conditions, in which the perimeter length is kept as large as possible while maintaining a large enough graphene nanoribbon width, a significant limitation exists for this device pattern.…”
Section: Patterning the Graphene At The Device Interfacementioning
confidence: 99%